2000
DOI: 10.1152/ajpregu.2000.278.4.r797
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient diet selection in thirteen mouse strains

Abstract: The strain distribution for macronutrient diet selection was described in 13 mouse strains (AKR/J, NZB/B1NJ, C57BL/6J, C57BL/6ByJ, DBA/2J, SPRET/Ei, CD-1, SJL/J, SWR/J, 129/J, BALB/cByJ, CAST/Ei, and A/J) with the use of a self-selection protocol in which separate carbohydrate, fat, and protein diets were simultaneously available for 26-30 days. Relative to carbohydrate, nine strains consumed significantly more calories from the fat diet; two strains consumed more calories from carbohydrate than from fat (BALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 33 publications
5
91
0
Order By: Relevance
“…This indicates that BALB/cJ mice have modifier genes which can rescue a defective leptin pathway. In the experiments of Alexander et al [1] and Smith et al [14], it was shown that BALB/cByJ mice ate less fat than B6 mice even when they were able to freely choose nutrients (protein, fat and carbohydrate), and body fat weight was lower in BALB/cByJ than in B6 mice.…”
Section: Strain Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…This indicates that BALB/cJ mice have modifier genes which can rescue a defective leptin pathway. In the experiments of Alexander et al [1] and Smith et al [14], it was shown that BALB/cByJ mice ate less fat than B6 mice even when they were able to freely choose nutrients (protein, fat and carbohydrate), and body fat weight was lower in BALB/cByJ than in B6 mice.…”
Section: Strain Factorsmentioning
confidence: 98%
“…C57BL/6J (B6) mice are commonly used for obesity research, because they are lean when they are fed a low fat diet, while they show obesity characteristics such as increasing body fat mass, hyperglycemia, and hyperinsulinemia when they are fed HFD [12,15]. BALB/cByJ mice eat less fat than B6, when they can freely access fat, protein or carbohydrate [14]. BALB/ cJ, which is another BALB/c substrain, has been used to investigate the genetic factors of diabetes and insulin resistance such as the ob/ob gene [11].…”
Section: Introductionmentioning
confidence: 99%
“…A major difference, however, between this experimental design and obesity in humans is that a large aspect of human susceptibility to obesity may not depend on the ability to resist weight gain when force-fed a high-fat diet. Rather, it may hinge on individual differences in the propensity to choose high-fat foods [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The C57BL/6J mouse strain is prone to weight gain under HF dietary conditions. 38 At the end of the fattening period, mice were divided into groups of equal body weight (mean7s.e.m. at time of implant ÂŒ 26.571.4 g).…”
Section: Introductionmentioning
confidence: 99%